The Prediction Number of Smear Acid Resistant Bacteria on Positive Pulmonary Tuberculosis Infection Disease at Madiun City in 2021 to 2025 - Avicena Sakufa Marsanti; Hanifah Ardiani (JURNAL INFO KESEHATAN, 2021)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium Tuberculosis Bacillus. The disease spreads in the air when people contract TB bacteria, such as coughing or sneezing. The lack of ability to anticipate the incidence of Acid Resistant Bacteria Positive Pulmonary TB in Madiun City is affected by the time and number of events that have not been appropriately foreseen. There is no map of regional vulnerability based on the time of occurrence. Hence, the incidence of Acid Resistant Bacteria Positive Pulmonary TB in Madiun city increases, determined by the total number of cases in 6 health centers, seven hospitals, and one prison. In 2015, there were 174 cases, then in 2019, 706 cases. The objective of this study is to predict the number of Acid Resistant Bacteria Positive Pulmonary TB suffering in 2021-2025 based on gender, health centers, and prisons in Madiun City and the overall incidence of cases in 2015-2019 is then foreseen in 2021 to 2025. This type of research is descriptive study research by employing Eviews with the ARIMA method. The population and samples in the study were all data of Acid Resistant Bacteria Positive Pulmonary TB case encompassing the sex of patients during 2015-2019 in Madiun City. The study aimed to predict the incidence of Acid Resistant Bacteria Positive Pulmonary TB in 2021-2025. The results of this study revealed the projection of Acid Resistant Bacteria Positive Pulmonary TB cases based on gender, health centers, hospitals, and prisons in Madiun City from 2020-2025, which experienced an increasing trend with the number of 933, 992, 1063, 1120, 1190 incidences respectively. This study is recommended for relevant agencies or health services to perform preventive efforts by involving trained policymakers and Health Cadis, particularly in preventing TB disease and reducing the high rate of predicting positive pulmonary TB smear incidences in the future.